Interaction of Temporal Lobe Epilepsy and Posttraumatic Stress Disorder: Network Analysis of a Single Case - Biran, Iftah; Admon, Roee; Gazit, Tomer; Fahoum, Firas (Frontiers in Psychology, 2020)
In this case study, we present a 21 years old female with long-standing Temporal Lobe Epilepsy (TLE) who, following a sexual assault, also developed Posttraumatic Stress Disorder (PTSD), leading to a change in her seizure semiology. The new seizures seemed to be a re-enactment of the sexual assault and accordingly were at first thought to be Psychogenic Non-Epileptic Seizures (PNES). Nevertheless, electroencephalography (EEG) recording at the Epilepsy Monitoring Unit (EMU) revealed ictal epileptic brain activity during these new attacks. In order to further explore the nature of the relation between epileptic seizures and PTSD symptomatology, a functional MRI (fMRI) scan was conducted focusing on neural response to threat (fearful faces). The results indicated that the response to threat elicited bilateral amygdala activation, as well as enhanced amygdala connectivity with the insula and anterior cingulate cortex (ACC), all central nodes of the fear circuitry. Accordingly, we suggest that this unique presentation of "pseudo" PNES might stem from the anatomical proximity of the epileptic network in this patient (temporal-insular-frontal) to the fear circuitry, allowing abnormal epileptic activity to "exploit" or activate the fear circuit or vice versa. We further propose that the traumatic experience may have changed the patient’s ictal semiology by modifying the course of the spread of the ictal activity towards the PTSD network.